Clinical Characteristics and Outcomes of Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder With Brainstem Lesions as Heralding Prodrome - Ji, Qiling; Dong, Huiqing; Lee, Hangil; Liu, Zheng; Tong, Yanna; Elkin, Kenneth; Haddad, Yazeed; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neurology, 2022)
Objective. The goal of the present study is todeterminethe clinical features, radiographic characteristics, and immune characteristics of serum and cerebrospinal fluid in multiple sclerosis and neuromyelitis optica patientswho present with prodromal brainstem lesions. Methods. We retrospectively studied 58 patients of multiple sclerosis (MS) and 52 patients of neuromyelitis optica spectrum disorder (NMOSD) with brainstem lesions as the prodromal event.Their gender, age, clinical features of the first onset, the expanded disability status scale (EDSS), the brain stem lesion upon the first onset by head MRI, and immune indexes of lumbar puncture cerebrospinal fluid were all evaluated.Results. The NMOSD group contained more femalepatients (4.8vs1.9，p<0.05), and was relatively older than theMS group (37.81±16.60vs27.57±11.17, p<0.001).NMOSD patients alsohad a significantly higher association withautoimmune diseases or positive autoimmune antibodies (P<0.01).There was no significant difference in the EDSS score between the two groups (P=0.420). Central hiccups, vomiting and the pyramidal tract sign were more common in the NMOSD group than the MS group, respectively (P<0.001, P<0.001, P<0.01). However, eye movement abnormalities were more frequent in MS group (P<0.01). There was no significant difference in other clinical manifestations, such as vertigo, diplopia, limb weakness, numbness, and eating difficulty. MS patients were more likely to have midbrain and pons imaging lesions (p<0.001,p<0.001), while NMOSD patients had more lesions in themedullary oblongata(p<0.001).The lesions in the MS group were mostly located in the periphery, while those in NMOSD group were centrally located(p<0.001,p< 0.001).Patchy lesions were more common in MS patients (p<0.001), while large lesions were more commonin the NMOSD group (P < 0.001). Finally, serum AQP4-Ab was only found in NMOSD group (P < 0.001). Conclusion. The patients with MS and NMOSD who were first diagnosed with brainstem lesions have differentiating clinical manifestations which include central hiccups,vomiting, pyramidal tract sign, and abnormal eye movement. Distinct imaging manifestationssuch as lesion location and morphology may also aid in initial, timelydiagnosis of MS and NMOSD.